Peripheral pnet of the inguinal region with favorable response to QT-Thalidomide Neoadjuvant: Pnet periférico de región inguinal con respuesta favorable a QT- Talidomida Neoadyuvante - Torvisco-Inca, Litze Dayné (2024)
Introduction: Primitive neuroectodermal tumours are a family of neoplasms that derive from the neural crest. They are classified into 3 groups: 1) central PNET, 2) Neuroblastoma and 3) peripheral PNET in peripheral nerves. The aim is to describe the characteristics of the case of a 32-year-old female patient who presented with an inguinal tumour with immunohistochemical profile for peripheral primitive neuroectodermal tumour. Case presentation: 32 year old female patient who presented with a tumour in the inguinal region, the biopsy indicated: small nuclei, hyperchromatic and monomorphous cell neoplasm, the immunohistochemical profile was: synaptophysin positive, neurofilament positive, SOX-11 positive and Ki-67: 70%. Conclusions: pPNTEs can occur in any extracerebral location, should be suspected in patients with round cell neoplasm, small blue. And request immunohistochemical markers: CD45, CD99, FLI-1, neurofilament, synaptophysin, chromogranin, SOX 11, myogenic markers and Ki 67. Keywords:  Groin, Neuroectodermal Tumors, Primitive, Peripheral (source: MeSH - NLM)